1973
DOI: 10.1113/jphysiol.1973.sp010331
|View full text |Cite
|
Sign up to set email alerts
|

The respiratory effects in man of altering the time profile of alveolar carbon dioxide and oxygen within each respiratory cycle

Abstract: SUMMARY1. Breathing hypoxic gas through an external dead space (ca. 1200 c.c.) stimulated ventilation disproportionately. A loop (ca. 250 c.c.) in the inspiratory pathway reduced the effect.2. The alveolar time patterns of P C02 and P02 characteristic of tube breathing with or without the loop have been simulated in moderate hypoxia by changing the composition of inspired gas at selected intervals after the beginning of inspiration.3. Supplying C02-free gas in late inspiration usually stimulated ventilation, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 33 publications
4
26
0
Order By: Relevance
“…The switching between the inspiratory lines was performed during expiration and was done by means oftwo remotely controlled solenoid-operated valves; a suction line was connected just upstream from the inspiratory valve flap in order to ensure that the new gas mixture would reach the subject quickly (Cunningham et al 1973). Three different types of test were performed: (A) 'Dummy' tests, in which the gases in the two lines were identical (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The switching between the inspiratory lines was performed during expiration and was done by means oftwo remotely controlled solenoid-operated valves; a suction line was connected just upstream from the inspiratory valve flap in order to ensure that the new gas mixture would reach the subject quickly (Cunningham et al 1973). Three different types of test were performed: (A) 'Dummy' tests, in which the gases in the two lines were identical (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The general arrangement of the apparatus was similar to that of Cunningham, Howson & Pearson (1973) except that breath-by-breath expired tidal volume VT was measured with a low-inertia wedge spirometer (Oxford Instruments Ltd, Osney Mead Industrial Estate, Oxford), and inspiratory, expiratory and total breath durations (TI, TE, TT) were recorded using the method of Gardner (1977).…”
Section: Methodsmentioning
confidence: 99%
“…An interesting observation reported that for a given increase in PETcoz, the magnitude of increase in ventilation was found to be greater in the tube than in C02 breathing (FENNER et al, 1968;CUNNINGHAM et al, 1973;METIAS et al, 1981). This evidence indicates a possibility that steady state values of PETco2 (or Paco2) cannot be used as an appropriate index for the level of C02-stimulus.…”
mentioning
confidence: 99%
“…A second possibility is that activity of the peripheral chemoreceptors is characteristically stimulated in such a manner that potentiation of afferent drives from three receptors may be exceeded in tube breathing than in C02 inhalation (GooDE et al, 1969;CUNNINGHAM et al, 1973).…”
mentioning
confidence: 99%
“…This stimulation has since been shown to be dependent upon a background of hypoxia (Goode, Brown, Howson & Cunningham, 1969), which suggests that the arterial chemoreceptors are involved. Further studies (Cunningham, Howson & Pearson, 1973) have shown that the human respiratory system can distinguish between small differences in the time pattern of alveolar CO2 but not of 02. These authors concluded that the arterial chemoreceptors are probably responsible for all these effects.…”
Section: Introductionmentioning
confidence: 99%